2012
DOI: 10.1057/rm.2012.7
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain risk management – I: Conceptualization, framework and planning process

Abstract: Supply chain risk management (SCRM) is an interdisciplinary emerging area of research crossing over operations management, finance and marketing, among other disciplines. Conceptualization of SCRM is argued in reference to previous studies on risk identification, risk assessment, supply chain vulnerabilities and risk management approaches used. A SCRM framework is then developed based on taxonomies defined for risk events and risk management approaches. In line with this framework, a risk management planning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 70 publications
0
24
0
1
Order By: Relevance
“…As there is a significant relationship between these three SCRM processes, more focus should be confined to three instead of two processes. Some researchers developed conceptual framework for the risk identification, assessment, and mitigation processes (Ritchie and Brindley, 2007;Foerstl et al, 2010;Bandaly et al, 2012;Kern et al, 2012;Ghadge et al, 2013). The five major components in their framework are risk identification, risk assessment, risk consequences, risk management response, and risk performance outcomes.…”
Section: Scrm Conceptual Frameworkmentioning
confidence: 99%
“…As there is a significant relationship between these three SCRM processes, more focus should be confined to three instead of two processes. Some researchers developed conceptual framework for the risk identification, assessment, and mitigation processes (Ritchie and Brindley, 2007;Foerstl et al, 2010;Bandaly et al, 2012;Kern et al, 2012;Ghadge et al, 2013). The five major components in their framework are risk identification, risk assessment, risk consequences, risk management response, and risk performance outcomes.…”
Section: Scrm Conceptual Frameworkmentioning
confidence: 99%
“…Networks confer both benefits and risks on firms. Supply chain risk management studies have found that alternative value chain business models (e.g., outsourcing, leaning, offshoring, and use of just‐in‐time models) generate different network configurations; in turn, these network arrangements can generate different risk propagation mechanisms across a value chain, affecting the level of exposure of individual actors to cascading impacts (Bandaly, Satira, Kahyaoglu, & Shanker, ; Otto, Willner, Wenz, Frieler, & Levermann, ; Punter, ; Scheibe & Blackhurst, Simchi‐Levi, Schmidt, & Wei, ). The type of relationship between two actors can influence whether risk will be transferred or absorbed by either one, or whether the risk will be shared.…”
Section: Theory and Conceptsmentioning
confidence: 99%
“…Third, as an innovative business model, SCF requires cooperation and collaboration between multiple participating companies with different characteristics. Under this circumstance, as the exposure profile of risks has been shifted from a single organization to the members within a "chain", the principle of supply chain risk management (SCRM), as stated by many authors [25][26][27], is applied. On one hand, the structure of SCF makes the participants more vulnerable to the traditional risks encountered by a single organization.…”
Section: Risk Managementmentioning
confidence: 99%